(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
Male dress in the post–French Revolution period was marked by the austerity of English tailoring, which came to shape bourgeois aesthetics from the nineteenth century to the present day. Men in major urban centers in Europe, Brazil, and the United States adopted the suit—comprising jacket, trousers, and waistcoat—as the visual synthesis of the Great Masculine Renunciation. Even the elaborate image of the nineteenth-century dandy reflected the black sobriety characteristic of the post–Industrial Revolution era. However, after the Second World War, a series of social and cultural movements led to the emergence of a new masculine aesthetic profile. The expansion of universities, the growth of prêt-à-porter consumption resulting from the consolidation of the urban middle class, and the strengthening of audiovisual media as social influencers gave rise to the figure of the young man, dressed in jeans and jackets and disseminated through images of cinema and music stars widely circulated in magazines, radio, and television programs. Confronting two distinct profiles—the functional sobriety of nineteenth-century menswear and the youth revolution of the postwar period—this article proposes a visual and theoretical panorama that systematizes the understanding of socioeconomic and cultural transformations, facilitating the teaching and learning of the history of menswear as a form of visual culture and as a creative tool in fashion practice.